2022
DOI: 10.1186/s12889-022-13076-1
|View full text |Cite
|
Sign up to set email alerts
|

Availability of medical cannabis services by racial, social, and geographic characteristics of neighborhoods in New York: a cross-sectional study

Abstract: Background Within the United States (US), because racial/ethnic disparities in cannabis arrests continue, and cannabis legalization is expanding, understanding disparities in availability of legal cannabis services is important. Few studies report mixed findings regarding disparities in availability of legal cannabis services; none examined New York. We examined disparities in availability of medical cannabis services in New York. We hypothesized that New York census tracts with few Black or Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…While previous studies pointed to cost as a significant challenge to certified patients prior to the pandemic (Zeng et al 2021 ; Zhu et al 2021 ), this burden was worsened due to newly added delivery costs and to financial vulnerability that participants experienced during the pandemic. In addition, the pandemic exacerbated disparities in access to medical cannabis services which previous studies identified in NY before the pandemic (Cunningham et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies pointed to cost as a significant challenge to certified patients prior to the pandemic (Zeng et al 2021 ; Zhu et al 2021 ), this burden was worsened due to newly added delivery costs and to financial vulnerability that participants experienced during the pandemic. In addition, the pandemic exacerbated disparities in access to medical cannabis services which previous studies identified in NY before the pandemic (Cunningham et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In NY as in other states, medical cannabis products are not covered by insurance and patients must pay for them with cash rather than credit or debit cards (New York City Department of Health and Mental Hygiene 2022 ). Certifying providers in NY are less likely to be located in areas with Black residents than in areas with other racial and ethnic compositions, and medical cannabis dispensaries are more highly concentrated in highly educated neighborhoods than in neighborhoods with less educated population (Cunningham et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Last, cannabisrelated tax revenue will be used to invest in communities most impacted by the war on drugs through social and economic equity programs implemented by local governments and community organizations. 47…”
Section: Evidence For Structural Factors Contributing To Racialized D...mentioning
confidence: 99%
“…45,46 For example, in 2021, New York state passed the Marijuana Regulation and Taxation Act, which includes three components designed to benefit communities that have been disproportionately affected by cannabis laws. 47 First, individuals convicted of a cannabis-related offense will have their convictions expunged. Second, the New York law stipulates that communities that have been disproportionately affected will have access to economic opportunities created by the law (e.g., cannabis licenses).…”
Section: Evidence For Structural Factors Contributing To Racialized D...mentioning
confidence: 99%
See 1 more Smart Citation